2019
DOI: 10.1186/s11658-019-0179-4
|View full text |Cite
|
Sign up to set email alerts
|

Costunolide reduces glycolysis-associated activation of hepatic stellate cells via inhibition of hexokinase-2

Abstract: Background Hepatic stellate cell (HSC) activation is a central event during hepatic fibrosis. Aerobic glycolysis is one of its metabolic hallmarks. Blocking glycolysis is a novel therapeutic option for liver fibrosis. This study investigated the effects of costunolide, a natural product demonstrated to have hepatoprotective effects, on HSC activation and glycolysis. Methods Primary HSCs were isolated from rats and cultured through 5 to 6 passages. Cell viability, activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…HK2, known as a pivotal rate-limiting enzyme, mainly regulates cell glycolysis. Targeting HK2 with costunolide decreased the uptake of glucose and lactate accumulation, resulting in suppression of hepatic stellate cell viability, which is the major cell for hepatic fibrosis (37). It has been demonstrated that glycolysis metabolism was associated with tumor cell development and progression in oral tongue squamous cell carcinomas (38).…”
Section: Discussionmentioning
confidence: 99%
“…HK2, known as a pivotal rate-limiting enzyme, mainly regulates cell glycolysis. Targeting HK2 with costunolide decreased the uptake of glucose and lactate accumulation, resulting in suppression of hepatic stellate cell viability, which is the major cell for hepatic fibrosis (37). It has been demonstrated that glycolysis metabolism was associated with tumor cell development and progression in oral tongue squamous cell carcinomas (38).…”
Section: Discussionmentioning
confidence: 99%
“…According to these findings, inhibitors of Hh signaling, HIF1α, glycolysis and lactate accumulation could be helpful to limit HSC activation and revert aHSCs to a quiescent state. Costunolide, a natural compound with anti-inflammatory, anti-oxidant and anti-tumor actions [57], has been recently shown to negatively modulate HSC activated phenotype, through inhibition of hexokinase 2, a ratelimiting glycolytic enzyme [58], which maintains glucose inside the cells as a source of energy metabolism [57]. Glutaminolysis is also essential to providing high levels of energy required by HSCs to maintain the activated phenotype [59].…”
Section: Limitation Of Hsc Activationmentioning
confidence: 99%
“…Focusing on HSCs, induction of apoptosis/senescence and reversion of activated HSCs are the main strategies [19]. Recent studies provide evidence that inhibition of aerobic glycolysis could attenuate the activation of HSCs [48,49]. Our findings suggest that the functional effects of STC1 in forming a feedforward loop to promote the fibrogenic process, partly via enhancing the glycolytic activity of HSCs.…”
Section: Discussionmentioning
confidence: 84%